Pemberdayaan Masyarakat melalui Budidaya Wortel yang Terintegrasi dengan Peningkatan Ekonomi - Lia Ira Sahara; Muhamad Eko Ari Wibowo; Chaeru Syahru Ramdani; Rananda Septanta (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service program was initiated in response to the need to enhance community economic resilience through sustainable agricultural practices. Limited utilization of residential land and lack of knowledge about integrated cultivation systems have hindered local economic potential. Therefore, this program aimed to empower the community through carrot cultivation integrated with economic improvement strategies. The activity was conducted on April 11, 2026, at Pamulang Permai Housing, West Pamulang, South Tangerang. The program involved 10 lecturers from Universitas Pamulang and was attended by 20 local residents. The implementation methods included lectures, hands-on practice, discussions, and question-and-answer sessions. The program was carried out in three stages: preparation, implementation, and reporting. The results showed an increase in participants’ knowledge and skills in carrot cultivation, including land preparation, planting, maintenance, and harvesting techniques. Participants also gained insights into simple business strategies and product value enhancement. Enthusiasm and active participation indicated the program’s positive reception, with potential for sustainable application to support household income. In conclusion, this program successfully contributed to community empowerment by integrating agricultural practices with economic development, fostering both self-sufficiency and entrepreneurship among residents.